Effect of a 6-month yoga intervention on heart rate variability among pre-diabetics - Saboo, Neha; Sudhanshu Kacker (International Journal of Health Sciences, 2022)
Objectives: Pre-diabetes represents the initial stage of type 2 diabetic disease. This study aimed to highlight the importance of the 6-month integrated approach of yoga therapy (IAYT) on the time domain and frequency domain of heart rate variability (HRV) in pre-diabetic subjects. Method: The study was conducted on 250 pre-diabetic adults aged 30–50 years attending a tertiary care hospital. The patients were divided into two groups: The study group (n = 125) was subjected to the IAYT and the control group (n = 125) was not engaged in yoga therapy. Biochemical parameters such as blood glucose, glycated hemoglobin, and the time domain and frequency domain of HRV were recorded at baseline and after 6 months of yoga intervention. Results: Participants had a mean age of 45.4 ± 6.4 years, the post-yoga intervention resulted in a significant decline in blood glucose, glycated hemoglobin, and significantly decreased frequency domain parameters low frequency (LF), and LF/high-frequency ratio (LF/HF ratio), and significantly increased in high frequency (HF) and in time-domain parameter standard deviation of normal-normal (NN) interval, mean percentage of differences higher than 50 ms in RR intervals (pRR50), and root mean square of successive differences between normal heartbeat (RMSSD). The number of pairs of successive NN (R-R) intervals that differ by more than 50 ms (NN50) significantly increased. Conclusion: The study clearly indicates that after 6 months of yoga intervention, autonomic nervous system shifted toward parasympathetic dominance, which was assessed by time domain and frequency domain parameters of HRV